2020
DOI: 10.34172/jrhs.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Adolescents Mental Health: A Multilevel Structural Equation Modeling (MSEM) Study in Northwest of Iran

Abstract: Background: We aimed to determine the relation of different sources of academic stress and adolescents´ mental health through mediator variables on the student and school levels. Study design: A cross-sectional study. Methods: Overall, 1724 students aged 12-19 yr were selected from 53 high schools in Qazvin City, northwest instead of central Iran through stratified cluster sampling. The sources of academic stress include family conditions, education system, future concerns, academic competitions, interaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
(36 reference statements)
0
11
0
3
Order By: Relevance
“…In the present study, an increased risk of AML was observed in approximately half of the cases who had a history of mental diseases, such as sadness, anxiety, depression, fear, and stress. It has been shown that the stress from the family is the most important source of stress associated with adolescent mental health 33 . No study has been conducted to explore the direct impact of mental disorders, including anxiety and depression, on AML incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, an increased risk of AML was observed in approximately half of the cases who had a history of mental diseases, such as sadness, anxiety, depression, fear, and stress. It has been shown that the stress from the family is the most important source of stress associated with adolescent mental health 33 . No study has been conducted to explore the direct impact of mental disorders, including anxiety and depression, on AML incidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some scholars have found that teenagers' mental health problems are related to their interpersonal relationships in school (Li et al, 2020a, b). The decline of mental health level is also related to high learning pressure (Hosseinkhani et al, 2020). Parents who use corporal punishment are more likely to develop mental health disorders in children (Durivage et al, 2015).…”
Section: Education Advicementioning
confidence: 99%
“…Considering that education is a person's path in work, of course there is high pressure in carrying out tasks both as students and students. A study shows that the academic field is a source of stress for youth students which can affect their mental health (Hosseinkhani et al, 2020). Academic stress is caused by various factors, such as personal inadequacy, fear of failure, interpersonal difficulties with teachers, teacher pupil relationships and inadequate study facilities were further analyzed and gender differences were also obtained (Reddy, Menon, & Thattil, 2018).…”
Section: Introductionmentioning
confidence: 99%